QUANTUM COMPUTING: REDEFINING THE FUTURE OF CYBERSECURITY LAWS AND REGULATIONS - Abdikhakimov, Islombek (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
Quantum computing, leveraging principles such as superposition and entanglement, introduces transformative capabilities with profound implications for cybersecurity. While promising to revolutionize industries, its potential to break widely used cryptographic protocols, such as RSA and ECC, presents an urgent challenge to existing cybersecurity frameworks. Current laws, designed for classical computing, are inadequate for addressing these emerging risks. This article examines the quantum threat landscape, the challenges in updating legislative frameworks, and the development of global regulatory strategies to ensure quantum-resilient security measures, emphasizing the critical need for proactive, collaborative policy reforms in the quantum era.